Reljina pećina (In situ, 2024)
The first archaeological investigation of Reljina pećina (Relja's cave), located on the coastal slope of southern Velebit, was carried out in November 2023. A preliminary typological analysis of the pottery suggested the use of the cave during the Neolithic, Eneolithic, Bronze Age and Middle Ages. The combination of archaeological research and conversations with shepherds from the immediate vicinity of the cave enabled the interpretation of the use of this speleological structure in recent and older periods.
Keywords: Velebit; Reljina pećina; prehistory; Middle Ages; ethnography